Mobile Adhoc Networks and Networking – An Overview of Existing Intrusion Prevention Techniques and Predictive Intrusion Prevention. (Global Journal of Computer Science and Technology, 2023)
Intrusion Prevention in computer networking refers to the set of techniques and technologies used to detect and prevent unauthorized access malicious activities and attacks on a network It involves actively monitoring network traffic identifying potential threats or anomalies and taking action to mitigate or block those threats In the realms of Mobile Adhoc Networks and general computer networking substantial work has pointed to the gaps experienced with respect to proactively identifying and mitigating risks and network malicious behaviours and attacks Further research was conducted to establish the current state of contemporary intrusion detection prediction and prevention techniques and their effectiveness to pro-actively identify and mitigate network attacks and malicious activity However it was found that the techniques utilized were very few or required futher accuracy improvements and for the identified effective techniques they required substantial amount of data processing power and a robust network architecture to support its implementation The work of this paper introduces the integration of the MANET Risk Scoring methodology based on Axiom theory into the realm of general networking All in an effort to increase the efficiency and accuracy of existing predictive intrusion prevention systems such as next generation Firewalls in corporate networks
Keywords: IDS; IPS; manets; attacks; anomalous; risk; malicious; prediction